Factors affecting the outcome of anaesthesia in surgically operated patients in two tertiary hospitals in Osun state, Nigeria - Adegoke, Adeola Omobola; Salawu, Rasidi A. (International Journal of Research in Medical Sciences, 2020)
Background: Few patients face surgery without some degree of anxiety. The concerns and fear vary from one person to another. Some may be anxious about the pain, disfigurement, incapacity and loss of control of self or death. The study investigated factors affecting the outcome of anaesthesia in surgically operated patients in two tertiary hospitals in Osun State, Nigeria. Methods: The study adopted a retrospective study design. Case file identification numbers of patients who had surgical operations under general anaesthesia between January 1st, 2015 and December 31st, 2019. The sample for this study consisted of 2,524 case notes purposely selected using purposive sampling technique. A checklist was developed which indicated all the variables needed from the patients case files. Data collected was analyzed using descriptive statistics of frequency and percentage. Results: The findings of this study showed that among the comorbidity of surgical operated patients, hypertension was mostly reported while the most prevalence risk behaviour was obstructive sleep, alcoholism, smoking, delay in waking up and delirium. Conclusions: It was also concluded that there is significant effect of age and gender on some comorbidity, risk behaviour of the anaesthesia process and outcome of anaesthesia. Based on the findings, it was recommended among others that the anaesthesia team must kindly investigate more on the patient before the commencement of anaesthesia during surgery.